Gambler ruin random walks and brownian motions in reserves modeling, application to pensions funds sustainability - Ferreira, M. A. M.; Filipe, J. (arXiv:2109.10313, 2025)
We used the random walk to model the problem of reserves. The classic case of a stochastic process is the example of random walks, which are used to study a set of phenomena and, particularly, as in this article, models of reserves evolution. Random walks also allow the construction of significant complex systems and are also used as an instrument of analysis, being used in the sense of giving a theoretical characteristic to other types of systems. Our goal is primarily to study reserves to see how to ensure that pension funds are sustainable. This classic approach to the study of pension funds makes possible to draw interesting conclusions about the problem of reserves.